Beyond the "Baartman Trope": representations of black women's bodies from early South African proto-nationalisms to postapartheid nationalisms - Van der Schyff, Karlien (Department of English Language and Literature, 2019)
In this thesis, I interrogate the discourses through which colonial stereotypes of race, gender and sexuality are uncritically invoked to serve new purposes, particularly in the service of postapartheid nationalist narratives. I argue not only that contemporary South African nationalism is imagined through gendered tropes, but also that the intersecting tropes of gender, race and sexuality which underlie postapartheid nation-building discourses propagate many of the same stereotypes about black women’s sexuality first entrenched through colonial representations. More specifically, I argue that these tropes are repeatedly invoked through an uncritical deployment of what I term the “Baartman trope”. With this term, I aim to signal the problematic discourses and systems of representation that have reduced Sara Baartman’s embodied specificity to that of a generalised, stereotypical symbol, either as the archetypal hypersexualised victim of colonial exploitation and humiliation, or as the symbolic mother of the “new” South African nation. Throughout this thesis, I not only offer a critique of the “Baartman trope” itself, but also aim to disrupt the decidedly reductive mode of representation which makes an essentialist stereotype such as the “Baartman trope” possible. To this end, I draw on performativity theory and the representational category of intimacy as ethical scholarly approaches to the politics of representation. I interrogate a wide range of literary texts, as well as a number of different scenes of representation that simultaneously challenge, perpetuate, refute and complicate essentialist and stereotypical representations of the black female body. Ranging from early South African proto-nationalist narratives to current postapartheid nationalist discourses, these different scenes of representation show that the same problematic tropes underlying colonial representations of gendered, racialised and sexualised black female bodies are more often than not re-imagined and reconstituted in the postcolonial imaginary. Furthermore, the fact that colonial systems of signification still underpin and influence postcolonial representations, albeit in new ways and to different purposes, highlights the inevitably ambiguous, unstable and hybridised nature of representing race, gender and sexuality in the South African postcolony.